Skrining fitokimia dan potensi daya hambat ekstrak pacing (Costus speciousus, J.Sm) terhadap Mycobacterium tuberculosis H37Rv - Puspaningtyas, Ayik Rosita (Faculty of Pharmacy, University of Jember, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis (Mtb) and can attack other body organs. Transmission occurs through splashes of phlegm when coughing, sneezing or talking. TB treatment using antituberculosis drugs (OAT) has side effects ranging from mild to severe side effects, namely hepatotoxicity. Therefore, alternative therapy from natural ingredients is needed because natural ingredients have few side effects when used appropriately. This research aims to determine the class of secondary metabolite compounds in the extract and fraction of the Pacing plant (Costus speciousus, J.Sm) and determine its effectiveness against Mycobacterium tuberculosis H37Rv. The extraction method used is remaceration with methanol solvent. The concentrations of the samples tested varied with the positive control of isoniazid. The research results showed that Pacing plant extracts and fractions contained alkaloids, flavonoids, saponins and tannins. Terpenoid compounds were not detected in the samples tested. The antituberculosis test showed that the n-hexane fraction had the best anti-TB activity, although the IC50 value of the extract and fraction was still lower than that of isoniazid as a positive control. However, Pacing extract and fraction still have potential as a very strong anti-TB agent because the IC50 value is below 50 ppm.